Comparison of the cardiac markers B-type natriuretic peptide and N-terminal pro B-type natriuretic peptide. (October 2009) - Buchner, Stefan; Jungbauer, Carsten; Birner, Christoph; Debl, Kurt; Riegger, Güünter A; Luchner, Andreas
B-type natriuretic peptide and N-terminal pro B-type natriuretic peptide have emerged as powerful biomarkers for heart failure and other cardiovascular conditions. B-type natriuretic peptide and N-terminal pro B-type natriuretic peptide are synthesized on the basis of myocardial stress and hypertrophy and are detectable in serum by several commercially available assays. Although both markers display wide similarities in their predictive values for acute and chronic heart failure, important differences exist regarding cutoff values and influence of noncardiac variables. The similarities and differences between B-type natriuretic peptide and N-terminal pro B-type natriuretic peptide will be reviewed and illustrated in detail regarding preanalytics and analytics, predictive properties for acute and chronic heart failure and prognosis as well as the influence of noncardiac parameters.